1997
DOI: 10.1002/(sici)1097-0215(19970317)70:6<639::aid-ijc2>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of estrone, estradiol and their sulfates, and evaluation of sulfatase and aromatase activities in patients with breast fibroadenoma

Abstract: In the present studies, the concentrations (mammary tissue and plasma) of estrone (E 1 ), estradiol (E 2 ) and their sulfates (E 1 S and E 2 S), as well as the sulfatase and aromatase activities, were evaluated in patients with breast fibroadenomas. Comparative studies of the evaluation of these parameters were carried out in: (A) tumor tissue, (B) areas surrounding the tumor and (C) areas distant from the tumor (glandular tissue) considered as normal tissue. The concentrations in the tumor tissue (in pmol/g t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 23 publications
3
54
1
3
Order By: Relevance
“…The organic upper phase was collected in a new tube and evaporated to dryness. The dry residue was neutralized with 0.5 mL NaHCO 3 (50 mM) [14].…”
Section: Acid Solvolysismentioning
confidence: 99%
See 1 more Smart Citation
“…The organic upper phase was collected in a new tube and evaporated to dryness. The dry residue was neutralized with 0.5 mL NaHCO 3 (50 mM) [14].…”
Section: Acid Solvolysismentioning
confidence: 99%
“…The use of radioimmunoassay (RIA) has been well documented in the literature. For routine analysis in clinical laboratories, several authors reported RIA methods [13][14][15][16][17][18]. We described, with accuracy and precision, a specific E 1 S radioimmunoassay involving a chromatographic purification C 18 step [13].…”
Section: Introductionmentioning
confidence: 99%
“…This supposition is based on evidence that in breast parenchyma the concentrations of estrone, free and conjugated, predominate over that of estradiol. 15,16 Hence, it is a tissue in which estrone can be assumed to be the principal primary estrogen available for aromatic hydroxylation. While this study was in progress, UGT2B7 was shown to also catalyze with high efficiency the glucuronidation of all-trans retinoic acid (atRA).…”
mentioning
confidence: 99%
“…In blood, elevated levels of estrogen were associated with the increased risk for breast cancer in both pre-and postmenopausal women (46,47). Furthermore, higher concentrations of estrogen were found in breast tumor tissue compared to normal breast tissue (48)(49)(50). Approximately two-thirds of all breast cancer patients were positive for ER, and could benefit from hormone therapy, but up to 50% of these cases had either de novo resistance or developed resistance during treatment (51,52).…”
Section: Estrogen and Breast Cancermentioning
confidence: 99%